Checklist of Sri Lankan weevils (Coleoptera: Curculionoidea: Curculionidae; excluding Scolytinae and Platypodinae): Based on literature data - Wijesinghe, Dilshara D.; Hong, Ki-Jeong (Zootaxa, 2025)
The checklist comprises 264 species in 122 genera and 10 subfamilies of the family Curculionidae (excluding the subfamilies Scolytinae and Platypodinae) recorded from Sri Lanka. Among these, 175 species are endemic or potentially endemic to Sri Lanka. The checklist includes synonyms, type localities, and species distributions across Sri Lanka, categorized by biogeographic zones and localities where available. The Central Province supports the maximum diversity of Curculionidae followed by the Nuwara Eliya District (94 species), Kandy District (40 species), and Matale District (19 species). The Anuradhapura District in the North Central Province exhibits the third-highest species diversity (23 species) of Curculionidae. Sitophilus linearis (Herbst) (Dryophthorinae: Rhynchophorini) and Rhinoncus paganus Gyllenhal (Conoderinae: Ceutorhynchitae: Phytobiini) are recorded for the first time from Sri Lanka.